2009
DOI: 10.1177/0748730409348551
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Entrainment of Drosophila’s Circadian Clock by Light and Temperature

Abstract: Daily light and temperature cycles are considered the most important zeitgebers for circadian clocks in many organisms. The influence of each single zeitgeber on the clock has been well studied, but little is known about any synergistic effects of both zeitgebers on the clock. In nature, light and temperature show characteristic daily oscillations with the temperature rising during the light phase and reaching its maximum in the late afternoon. Here, we studied behavioral and molecular rhythms in Drosophila me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
100
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 53 publications
10
100
0
1
Order By: Relevance
“…Interestingly, D. melanogaster exhibits a strong preference for a temperature rhythm in which the temperature is lower in the morning and higher at dusk: The preferred temperature increases gradually from morning (ZT1-3) to peak in the evening (ZT10-12) (53). A similar synergistic effect was described in flies, in which a combination of light and temperature zeitgebers reinforced entrainment at the molecular and behavioral level (54). In our current study, the phase relationship to the LD/ CW cycle showed a marked dependency on temperature, reflecting some adaptive aspects of the rhythm related to the natural environment of the nematode.…”
Section: Discussionsupporting
confidence: 49%
“…Interestingly, D. melanogaster exhibits a strong preference for a temperature rhythm in which the temperature is lower in the morning and higher at dusk: The preferred temperature increases gradually from morning (ZT1-3) to peak in the evening (ZT10-12) (53). A similar synergistic effect was described in flies, in which a combination of light and temperature zeitgebers reinforced entrainment at the molecular and behavioral level (54). In our current study, the phase relationship to the LD/ CW cycle showed a marked dependency on temperature, reflecting some adaptive aspects of the rhythm related to the natural environment of the nematode.…”
Section: Discussionsupporting
confidence: 49%
“…Consistent with this last scenario, an impact of environmental temperature oscillations on circadian rhythm regulation has been documented in a number of insects including cave-adapted carabid and catopsid beetles (for reviews, see Lamprecht and Weber, 1992;Page, 1985;Rence and Loher, 1975;Tomioka and Chiba, 1989;Weber et al, 1995;Yoshii et al, 2009 Mammoth cave system but entrance areas, exposed to air currents, show variation in humidity and temperature (Barr and Kuehne, 1971). Moreover, there is evidence that the distribution of bottomdwelling cave arthropods including P. hirtus is temperature and humidity dependent (Barr and Kuehne, 1971).…”
Section: Discussionmentioning
confidence: 81%
“…While it is tempting to speculate that P. hirtus measures diurnal light level changes in the disphotic cave environment, the clock gene network may be environmentally adjusted by other stimuli such as temperature (Collins et al, 2004;Yoshii et al, 2009). Consistent with this last scenario, an impact of environmental temperature oscillations on circadian rhythm regulation has been documented in a number of insects including cave-adapted carabid and catopsid beetles (for reviews, see Lamprecht and Weber, 1992;Page, 1985;Rence and Loher, 1975;Tomioka and Chiba, 1989;Weber et al, 1995;Yoshii et al, 2009 Mammoth cave system but entrance areas, exposed to air currents, show variation in humidity and temperature (Barr and Kuehne, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…The daily oscillations of clock proteins, such as period (PER) and timeless (TIM), are quite well synchronized in all circadian neuron groups (16,17). However, their diverse functions suggest that their peak neuronal activities, when they achieve maximal firing rates, occur at different circadian times.…”
mentioning
confidence: 99%